2004
DOI: 10.1158/0008-5472.can-04-3703
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of Human Bronchial Epithelial Cells in the Absence of Viral Oncoproteins

Abstract: By expressing two genes (hTERT andCdk4

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
622
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(639 citation statements)
references
References 25 publications
16
622
0
1
Order By: Relevance
“…MRC5 cells were grown in Minimal Essential Medium (Biological Industries) supplemented with 10% non-heatinactivated fetal bovine serum, MEM-Eagle's nonessential amino acids, sodium pyruvate, L-glutamine and antibiotics. HBECs immortalized with hTERT+Cdk4 51 were grown in keratinocyte serum-free medium (Invitrogen, Grand Island, NY, USA) supplemented with 50 μg/ml bovine Pituitary extract and 5 ng/ml hEGF (Invitrogen). 52 5′aza-deoxycytidine (5′aza; MP Bio-Med, Santa Ana, CA, USA) was dissolved in acetic acid:H2O.…”
Section: Methodsmentioning
confidence: 99%
“…MRC5 cells were grown in Minimal Essential Medium (Biological Industries) supplemented with 10% non-heatinactivated fetal bovine serum, MEM-Eagle's nonessential amino acids, sodium pyruvate, L-glutamine and antibiotics. HBECs immortalized with hTERT+Cdk4 51 were grown in keratinocyte serum-free medium (Invitrogen, Grand Island, NY, USA) supplemented with 50 μg/ml bovine Pituitary extract and 5 ng/ml hEGF (Invitrogen). 52 5′aza-deoxycytidine (5′aza; MP Bio-Med, Santa Ana, CA, USA) was dissolved in acetic acid:H2O.…”
Section: Methodsmentioning
confidence: 99%
“…Primary podocytes, after two passages, were infected with retrovirus carrying CDK4 (22) or SV40 large T antigen mutant tsA58U19 (11,27) with 8 g/ml polybrene. Beginning after 72 h, cells were treated with 0.2 mg/ml G418 at 37°C (CDK4) or 33°C (tsA58U19) for 14 days.…”
Section: Glomerular Isolationmentioning
confidence: 99%
“…The kinase activity of CDK4 is specifically involved in progression through G1, via phosphorylation of retinoblastoma (Rb) family members (4). Recently, Ramirez et al (22) immortalized human bronchial epithelial cells by ectopic expression of CDK4 and human telomerase (hTERT). Microarray analysis showed that CDK4/hTERTimmortalized cells showed significantly different gene expression profiles compared with cells immortalized with human papiloma viral oncoproteins E6/E7 or SV40T and that CDK4-transformed cells clustered with primary bronchial epithelial cells.…”
mentioning
confidence: 99%
“…Over-representation of the entire 5p arm was a recurrent event in both cell types with the telomeric end of 5p15.33 showing the greatest amount of change. This region contains the telomerase reverse transcriptase (hTERT) gene which has been implicated in cell immortalisation in numerous cancers (Tomoda et al, 2002;Ramirez et al, 2004). Gain of the 11q13.1 -11q14.1 region was present in 450% of the lung cancer cell lines with the highest degree of concordance at 11q13.3 (Figure 2).…”
Section: Regions Of Similaritymentioning
confidence: 99%